An estimation of the X/Q value for the first Philippine Nuclear Power Plant (PNPP-1) - Marcelo, Veronica J. (1985)
Atmospheric transport and dispersion of gaseous effluents in routine releases from the first Philippine Nuclear Power Plant (PNPP-1) were determined using the XOQDOQ computer code. This code is a computer program which calculated average relative effluent concentrations (X/Q's) and average relative disposition values (D/Q's) at locations specified by the user, and at standard radial distances and segments for downwind sectors for routine plant releases. The input data utilized for the estimation of atmospheric transport and dispersion are based on the information gathered from the Final Safety Analysis Report (FSAR) and the Environmental Report (ER) for the first Philippine Nuclear Power Plant.
The objective of the study is to provide conservative estimates of average relative effluent concentrations (X/Q) at distance out to 80 km from the PNPP-1. In order to provide estimates of annual average atmospheric dilution factors, the Constant Mean Wind Detection Model outlined in Section C (excluding Cla and Clb) of Regulatory Guide 1.111, "Methods for Estimating Transport and Dispersion of Gaseous Effluents in Routine Releases from Light-Water Cooled Reactors) was applied to the four years Napot Point Meteorological data base incorporating the PNPP-1 design parameters. The dilution factors were calculated using a ground level release for 16 cardinal directions at distances extending from exclusion area boundary to 80 km from PNPP-1. Radioactive decay and relative deposition were also considered in making the X/Q estimates. The joint frequency distribution speed and direction categories by stability class was used as the meteorological data input for calculating the annual average X/Q values. The computer output gives the calculations of annual average X/Q at distances ranging from 0.4 km (0.25 miles) to 80.5 km (50 miles) over the 16 direction sectors. For corresponding distances and sectors annual average relative deposition per unit area (D/Q) values (meters^-2) are listed. Calculation of X/Q values and D/Q of the different receptor types within 10 km from the site are also given. Modelling assumptions used for the calculations are: a) Ground level release for a vent height of 57 meters b) negligible exit velocity c) wind measurement taken at 10 meters d) height of the vent's building of 57 meters and cross-sectional area of 2140 square meters.
Mimeographed.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman.
Keywords: Philippine Nuclear Power Plant (PNNP-1).; Radioactive fallout -- Mathematical models. -- Philippines -- Bataan; Radioactive waste disposal -- Mathematical models. -- Philippines -- Bataan